Analisis Pengaruh Budaya, Kelas Sosial, Psikologis, Harga dan Promosi Terhadap Keputusan Studi Lanjut ke Program Sarjana Bidang Studi Akuntansi - Setiawanta, Yulita (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
This study aims to determine the factors that influence the students decision in choosing further study at university, especially choosing to study accounting program S1 FEB UDINUS Semarang. The factors used in the study is Cultural Factors, Social Class, Psychological, Price and Promotion. These factors are also relevant to factor in the marketing mix, where the accounting courses are also interested to know the background of the decision of the selection offurtherstudy. The population in this study were all freshmen courses accounting S1 FEB Force UDINUS year 2012-2013 as many as 267 students. Sample representativeness approach with Slovin formula obtained 160 samples, but the data are processed only 159 samples only. Distribution of questionnaires to the sample using random sampling method, in which samples randomly encountered. Data quality test reliability and validity, test assumptions Classical, Regression Test,ANOVA and coefficient determinant. The results obtained are factors Culture, Social Class and Promotion does not significantly influence the decision studui further. While the price factor and the Psychological Impact of the decision signifikasn further studies.Perfect model with sig. 0.000, coefficient determinant inthevalue of 49.10 percent.